2016
DOI: 10.1371/journal.pone.0166232
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Economic Impact of Probiotics Consumption on Respiratory Tract Infections: Projections for Canada

Abstract: IntroductionThere is accumulating evidence supporting the use of probiotics, which are defined as “live micro-organisms which, when administered in adequate amounts, confer a health benefit on the host”, as a preventive measure against respiratory tract infections (RTI). Two recent meta-analyses showed probiotic consumption (daily intake of 107 to 1010 CFU in any form for up to 3 months) significantly reduced RTI duration, frequency, antibiotic use and work absenteeism.ObjectivesThe aim of this study was to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…Although there is in general no doubt for the probiotic efficacy, the strain specificity is underlined as well as the importance of having strain-specific evidence for efficacy and safety, generated and confirmed in welldesigned randomised clinical trials. Moreover, based on health-economic analyses, it was reported that probiotics can substantially reduce the socioeconomic burden associated with common upper respiratory tract infections experienced by both adults and children [5,6]. The combination of Lactobacillus plantarum HEAL9 and Lactobacillus paracasei 8700:2 has previously been shown to reduce the incidence, duration and severity of common colds in adults [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is in general no doubt for the probiotic efficacy, the strain specificity is underlined as well as the importance of having strain-specific evidence for efficacy and safety, generated and confirmed in welldesigned randomised clinical trials. Moreover, based on health-economic analyses, it was reported that probiotics can substantially reduce the socioeconomic burden associated with common upper respiratory tract infections experienced by both adults and children [5,6]. The combination of Lactobacillus plantarum HEAL9 and Lactobacillus paracasei 8700:2 has previously been shown to reduce the incidence, duration and severity of common colds in adults [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to dietary prescriptions based on microbiome bioinformatics [97], other microbe-derived therapies are on the horizon. Already, probiotics, prebiotics, and postbiotics (e.g., heat-inactivated microbes or microbial parts) are being utilized for personal and public health benefit [98][99][100][101][102][103]. Fecal microbiota transplant, already of known value in Clostridium difficile infection [104], may provide benefit in various extra-intestinal NCDs [105,106].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Specific probiotics have been suggested to be effective in alleviating the duration and severity of acute rotavirus gastroenteritis [ 14 , 15 ]. In addition, probiotics are able to reduce the risk of respiratory tract infections [ 7 , 16 ] which in most cases are of viral origin. Probiotics are likely to have an impact through gut mucosa by balancing the local microbiota [ 17 ], by inhibiting the growth of pathogenic microorganisms [ 18 ], and by enhancing local and systemic immune responses [ 19 ].…”
Section: Discussionmentioning
confidence: 99%